IMPLEMENTATION OF HIGHER ORDER THINKING SKILLS (HOTS) IN WRITING EXERCISES ON THE COMPULSORY ENGLISH TEXTBOOK - Fatihatun Nurfazura; Ria Kamilah Agustina (Program Studi Pendidikan Bahasa Inggris, 2024)
This research is qualitative, especially content analysis. The data collection technique used in this research is document analysis. The document used in this study is an English textbook entitled “Bahasa Inggris SMA/MA/SMK/MAK” for Class XII, published by the Indonesian Ministry of Education and Culture 2018. This research aimed to get empirical evidence of the distribution of higher-order thinking skills based on the revised edition of Bloom’s Taxonomy. The data analysis technique proposed by Miles and Huberman involves data reduction, data presentation, and conclusion. The results show that the higher-order thinking skills in writing exercises in this textbook only obtained 9 out of 21 questions (42.8%), while the lower-order thinking skills obtained 12 out of 21 questions (57.1%). It can be concluded that the distribution of the higher-order thinking skill is lower than the lower-order thinking skill. The distribution of the higher-order thinking skill looks like this: the analyze skill (C4) obtains two questions (9.5%). The evaluate skill (C5) receives two questions (9.5%), and the Create skill (C6) gets the highest distribution by obtaining 5 out of 9 questions (23.8%). It shows that the distribution of the higher-order thinking skill of writing exercises in the English textbook “Bahasa Inggris SMA/MA/SMK/MAK” is unequal. It does not show the higher-order thinking skills properly. Furthermore, this statement is supported by the unequal distribution of writing exercises in each textbook chapter.